Piroplasms in farmed American bison, Bison bison from Romania - Corduneanu, Alexandra; Taulescu, Marian; Ursache, Teodor Dan; Ionică, Angela Monica; Mihalca, Andrei Daniel (Frontiers in Veterinary Science, 2023)
The American bison (Bison bison) is the largest terrestrial mammal of North America, with around 350.000 individuals in the wild and in private herds and but the knowledge regarding the presence of different vector-borne parasites pathigens in these mammals is very scarcepoor. Babesia and Theileria spp. are tick-borne apicomplexan parasites which are considered to be among the most commonly found blood parasites of large ruminants, often with a high economic importance. However, the knowledge on piroplasms of bisons is extremely scarce. The aim of our study was to evaluate the presence of protozoan apicomplexan parasites in blood and tissues of farmed American bison from Romania. Overall, we tested 222 blood samples and 11 tissues samples (heart, liver and spleen) from farmed B. bison raised for meat in Romania. All the samples were analysed by nPCR targeting the 18SrRNA gene for piroplasmids. All positive samples were sequenced and analysed phylogenetically. The overall prevalence of infection with piroplasmids in American bison was 1.65%, with Babesia divergens and Theileria sp. identified following sequencing. To our knowledge, this is the first report of piroplasms detected in blood and tissues of farmed B. bison from Europe. Further studies are necessary in order to obtain a better overview on the epidemiological status and clinical relevance of piroplasms in farmed American bisons.